Technical report: determine the relative efficiency of faculties by using data envelopment analysis / Nur Amirah Ashaari, Nur Syahirah Mohmd Yusoff and Nurul Shamila Mansor - Ashaari, Nur Amirah; Mohmd Yusoff, Nur Syahirah; Mansor, Nurul Shamila (2016)
The purpose of this project paper is to evaluate the relative efficiency of faculties in a university. Universities have a main function in the process of producing high quality product to the nations and citizens. Along the process, the need of financial assistance is important to the management since government subsidies for education sector have been reduced. Therefore, the universities have to ensure that resources are fully utilized. In order to determine either the organization operates efficiently or not, performance measurement is such a thing to think about. Various methods have been introduced to aid the measurement of the relative efficiency. The main approaches employed in this research is by using Data Envelopment Analysis (DEA). The faculties of a public university in Malaysia, which is Universiti Teknologi MARA (UiTM) were selected as the Decision Making Unit (DMU). The relative efficiency of a DMU is determined through the method of comparing the efficiency between a DMU with other DMUs. Three inputs and two outputs have been assigned in this project such as number of registered students, number of academic staffs and also number of non academic staffs for inputs, while number of graduates and average results for outputs. Throughout this project, only 6 faculties were classified as efficient, and the remaining 17 faculties were inefficients. For the inefficient faculties to improve, 6 efficient faculties were set as the benchmark. This research also provide some information on how the management of inefficient faculties can act in order to improve the faculties into a better level of efficiency.